1 V CMOS current references for wide‐temperature range applications. Issue 17 (1st August 2013) - Calvo, B.; Azcona, C.; Medrano, N.; Celma, S.
Abstract : Two new low‐voltage micropower first‐order temperature‐compensated CMOS current references are presented. To achieve compact architectures able to operate under low voltage with low power consumption, the references are based on the simplest approach of cross‐coupled current mirrors, and compensation is obtained by introducing a temperature‐dependent current mirror ratio. Results for 0.18 µm CMOS implementations show that the proposed 1 μA references operate with supplies down to 1 V showing temperature drifts below 231 ppm/°C over a (from –40 to 120°C) range.